Recombinant-activated factor VII in the paediatric cardiac surgery: Single unit experience - Vijay Agarwal; Kelechi E Okonta; Praveen S Lal (Wolters Kluwer Medknow Publications, 2012)
Background: The control of excessive bleeding after paediatric cardiac surgery can be challenging. This may make the use of recombinant-activated factor VII (rFVIIa) in preventing this excessive bleeding, after adopted conventional methods have failed, desirable. Our aim is to highlight our experience with the use of rFVIIa in preventing excessive bleeding after paediatric cardiac surgery. Patients and Methods: The data for 14 patients who had rFVIIa for excessive haemorrhage after cardiac surgery from December 2009 to November 2010 was analysed. The perioperative blood loss from the chest drain before and after the administration of rFVIIa, use of blood products, international normalized ratio (INR) and activated partial thromboplastin (aPTT), before and after administration of rFVIIa, were analysed. Results: The rFVIIa was successful in stopping bleeding in all the patients. The mean coagulation factors before rFVIIa were as follows: INR, 2.88 (1.82-4.5); aPTT, 65 seconds (33.4-95.1); after rFVIIa, the mean INR was 1.2 (0.82-1.56), mean APTT was 38.7 seconds (25.6-54.9). No thromboembolic events or allergic reactions or deaths were recorded. Conclusions: rFVIIa use is not only effective in stopping excessive perioperative bleeding but also safe and indirectly reduces transfusion of blood and its products.